Features of the Formation of the Grammatical Skills in Teaching Foreign Languages to Students of the Technical Universities (Texas Journal of Multidisciplinary Studies, 2022)
The article deals with the issues of creating relevant skills in teaching Grammar, as integral part, in learning foreign languages. According to the authors, grammar mastering plays an important role in teaching foreign languages, since an insufficient level of grammatical skills formation hinders the formation of not only skills and abilities of other aspects of the language, but also communicative competence in general. The authors identify several problems in teaching these skills.